Daily variation feeding of Astyanax lacustris (Lütken 1875) in a subtropical river (Acta Scientiarum. Biological Sciences, 2021)
This study aimed to know the daily variation of Astyanax lacustris (Lütken 1875) feeding in a lotic environment. Fish were caught with a net for cici4d three days every three hours in the summer to capture ten individuals per hour in a stretch of the Ijuí River, Middle Uruguay River, Brazil. The captured specimens had their stomachs removed and the content analyzed and separated into seven food categories with the aid of stereomicroscope. For the analysis of food items were used the frequency of occurrence methods, volumetric method and applied the Alimentary Index (IAi). Two hundred stomachs were analyzed, of which 95% had food content. The most abundant items were algae and autochthonous insects. Astyanax lacustris feeds throughout the day especially early in the morning (9 hours) and reduces its feeding at night (24 hours and 3 hours). It was also verified variation of AI of different food items throughout the day cici4d. It is concluded that A. lacustris feeds throughout the day, especially in the daytime and that throughout the 24 hours it varies its diet due to photoperiod and food availability.